Speech Corpora, Feature Extraction Techniques and Classifiers with Special Reference to Automatic Speech Recognition - Dutta, D; Choudhury, RD; Gogoi, S (International Journal of Computer Sciences and Engineering, 2019)
in the current years, speech recognition has emerged as an important research area. To carry out further research on automatic speech recognition, a comprehensive review of existing work in this domain stands useful and constructive for the researchers. This paper has presented a recent literature review on speech recognition considering various existing speech corpora, speech features and different models or classifiers used in speech recognition. Different speech databases have been compared in terms of the number of speakers, type of speakers such as native or acted, age and gender of speakers and speech recording environment. Various techniques for speech signal acquisition and pre-processing of the speech signals are also addressed in this work.